VITAMINS PROVOKE THE RELEASE OF NITRIC OXIDE BY SODIUM NITROPRUSSIDE: IN VITRO STUDY - Ali, Eham A (Al-Nahrain Journal of Science, 2010)
It is plausible to assume that vitamins act as nitric oxide scavengers or donors like cobalaminederivatives. Therefore, this study aimed to screen the effect of folic acid, hydroxycobalamine andphytomenadione on nitrogen species. The effects of hydroxyl cobalamine, folic acid andphytomenadione were studied on the synthesized peroxynitrite as well as on their ability to generateperoxynitrite. It is ability to donate nitric oxide or to scavenge released nitric oxide by sodiumnitroprusside (10mM) also investigated in vitro experimental model. Synthetic peroxynitrite wasscavenged by folic acid, hydroxycobalamine and phytomenadione. Their effects varied with theirconcentrations. These vitamins per se failed to release nitric oxide while they improved thebioavailability of nitric oxide released by 10 mM sodium nitroprusside. The beneficial effects offolic acid and to less extent hydroxycobalamine and phytomenadione in improving the nitric oxidebioavailability raise the idea of using these substances as adjunct therapy in diseases associated with endothelial dysfunction.